PELUANG DAN TANTANGAN OBLIGASI SYARIAH DI INDONESIA: SEBUAH TINJAUAN KONSEPTUAL - Wicaksana, Moch. Zulfiqar Agung (Jurnal Akuntansi AKUNESA, 2014)
With increasing wave of popularity and successes of Islamic finance across the world, Indonesia aspires to adaptation of this Islamic finance. Islamic bond or called sukuk as a new alternative for micro financing in Islamic financial institutions. This study aims to analyze opportunities and challenges of Islamic bond (sukuk) in Indonesia. In other country sukuk usually used as a solution to way out from economy crisis. Keywords: Islamic bonds, sukuk, Islamic finance, opportunities and challenges, economy crisis